Bilateral Laparoscopic Stone Surgery for Renal Stones- A Case Series - Nouralizadeh, Akbar; Kashi, Amir H; Valipour, Reza; Nasiri Kopaee, Mahmood Reza; Zeinali, Mahdi; Sarhangnejad, Reza (Urology Journal, 2017)
Purpose: To present our experience with synchronous or metachronous laparoscopic pyelolithotomy and ureterolithotomy for patients with bilateral urolithiasis. Materials and Methods: The data of all patients who underwent laparoscopic pyelolithotomy (± ureterolithotomy) for bilateral renal and/or ureteral stones from November 2009 to July 2014 were included. Laparoscopic operations were performed through a transperitoneal approach. Results: 10 patients underwent laparoscopic operations for renal stones (19 kidney stones) and ureteral stones (1 ureteral stone). 4 patients underwent synchronous operations and 6 patients underwent metachronous operations. The mean ± SD of operation duration were 212 ± 51 minutes for synchronous operations and 166 ± 41 minutes for metachronous operations. Residual stone was observed 5 patients. No patient developed urinary leakage. Conclusion: Laparoscopic pyelolithotomy and/or ureterolithotomy for bilateral stones is a feasible option in centers with experience in laparoscopy.